World Crisis and Inflation Processes of Recent Years: Causes and Consequences - Nataliia BLENDA; Inna CHERNEHA; Mykola KOROTIEIEV; Olena ZHARUN; Oleksandr Nepochatenko; Volodymyr ULANCHUK (Communications of International Proceedings, 2023)
The article is devoted to the study of the period of the greatest crisis and the greatest inflationary growth in the last three decades. Particular attention in the research is given to defining the features of the current crisis, establishing the cause of the emergence and development of inflation, and its impact on the economy of different countries. Most studies link the current crisis to the COVID-19 pandemic. However, COVID-19 cannot be considered the main cause of the global economic crisis. Rather, COVID-19 has become an accelerator and exacerbated the global financial crisis. The first manifestations of the crisis are noted in February-April 2020 during the fall of the world stock market. In 2022, the situation worsened due to the start of the war in Ukraine and large-scale sanctions against Russia. The current crisis and inflation has a much broader basis, primarily the rise in energy and food prices. Among the factors that aggravate the crisis, the supply chain crisis should be singled out, which indicates both a long-term effect and global consequences. The consequences of the crisis are a sharp increase in the number of unemployed, inflation and uncontrolled price growth, the bankruptcy of a large number of enterprises, etc. A high level of inflation is a great threat to production, causing economic and social tension in society. Today, there is no country that has not experienced losses and economic shocks due to inflationary processes, since the consequences of inflation are complex and diverse.
Keywords: Inflation; Crisis; Price Growth; World Economy.